2020
DOI: 10.3390/molecules25102299
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Electrical Characteristics of Perovskite Solar Cells with Aging Time

Abstract: The last decade has witnessed the impressive progress of perovskite solar cells (PSCs), with power conversion efficiency exceeding 25%. Nevertheless, the unsatisfactory device stability and current–voltage hysteresis normally observed with most PSCs under operational conditions are bottlenecks that hamper their further commercialization. Understanding the electrical characteristics of the device during the aging process is important for the design and development of effective strategies for the fabrication of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…The carrier recombination behaviour was further assessed by the semilogarithmic J-V curve in the dark (Figure 4e). By fitting the exponential region of the curve with the Shockley equation that is given by [45][46]…”
Section: Resultsmentioning
confidence: 99%
“…The carrier recombination behaviour was further assessed by the semilogarithmic J-V curve in the dark (Figure 4e). By fitting the exponential region of the curve with the Shockley equation that is given by [45][46]…”
Section: Resultsmentioning
confidence: 99%
“…Some papers reported the value of ideality factor for aged and pristine devices, suggesting that the unity value of n indicates the dominance of recombination at the surface of the perovskite film, whereas n id < 2 refers to trap-assisted Shockely-Read-Hall (SRH) recombination in the perovskite bulk. 46,67 Authors found that for aged devices was dominant SRH recombination. For our devices the ideality factor was calculated from the slope of V oc vs ln( ph /) reported in Fig.…”
Section: Dark J-v and Ideality Factormentioning
confidence: 99%
“…In literature several studies have been made to measure the charge transfer, such as time-of-flight secondaryion mass spectrometry, glow discharge optical emission spectrometry, transient photovoltage decay measurements and electrochemical impedance spectroscopy. 21,22,67,[72][73][74] These analyses could give more information on charge transport in PSCs especially when hysteresis-free devices are obtained. Further investigation could be planned to study ambient air stored devices adding information on charge recombination when PV parameters increase over time, by linking results with fabrication and storage processes.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…However, traditional solar energy utilization devices have relatively high costs and low efficiencies and are less economical than conventional energy sources, which severely restricts the use of solar energy. 1–6 As the third-generation solar cell, the photoelectric conversion efficiency of perovskite solar cells (PSCs) has increased rapidly in the past decade. 7–10 Moreover, PSCs are rich in synthetic raw materials with a relatively low preparation cost, providing a more feasible approach for low-cost and high-efficiency solar energy utilization.…”
Section: Introductionmentioning
confidence: 99%